2022
DOI: 10.1101/2022.02.02.478845
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oncogenic protein condensates suppress growth factor perception and modulate drug tolerance

Abstract: Drug resistance remains a central challenge towards durable cancer therapy, including for cancers driven by the EML4-ALK oncogene. EML4-ALK and related fusion oncogenes form cytoplasmic protein condensates that transmit oncogenic signals through the Ras/Erk pathway. However, whether such condensates play a role in drug response or resistance development is unclear. Here, we applied optogenetic functional profiling to examine how EML4-ALK condensates impact signal transmission through transmembrane receptor tyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…We validated this fast decay through a fixed-cell time course experiment and obtained similar fast decay of the EML4-ALK/CluMPS condensates (t 1/2 = 3.5 minutes) ( Supplementary Figure 10 ). This faster measured rate may reflect the differences in measuring endogenous aggregates versus aggregates of overexpressed EML4-ALK, as performed previously 79 . We also observed that, despite extended drug treatment, ALKi did not induce full dissociation of CluMPS condensates, in line with previous reports showing that EML4-ALK (V1) condensates are relatively stable 10, 80 .…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…We validated this fast decay through a fixed-cell time course experiment and obtained similar fast decay of the EML4-ALK/CluMPS condensates (t 1/2 = 3.5 minutes) ( Supplementary Figure 10 ). This faster measured rate may reflect the differences in measuring endogenous aggregates versus aggregates of overexpressed EML4-ALK, as performed previously 79 . We also observed that, despite extended drug treatment, ALKi did not induce full dissociation of CluMPS condensates, in line with previous reports showing that EML4-ALK (V1) condensates are relatively stable 10, 80 .…”
Section: Resultsmentioning
confidence: 63%
“…The ability to visualize endogenous aggregates allowed us to track their dynamics in response to the ALK inhibitor crizotinib ( Figure 5F, Supplementary Figure 11, Supplementary Movie 4 ). Although it is known that crizotinib blocks EML4-ALK activity and suppresses its condensation, in part due to dissociation of Grb2 10, 79, 80 , the kinetics and extent of condensate dissolution has not been observed in living cells. We found that, upon drug addition, CluMPS condensate area rapidly decreased within 10 minutes, followed by a slow but measurable decrease thereafter ( Figure 5G, Supplementary Figure 11 ).…”
Section: Resultsmentioning
confidence: 99%
“…Resistance to cancer therapies like cirzotinib against fusion oncogenic proteins, such as EML4-ALK in non-small cell lung cancer (NSCLC), can be explained by a localizer c-mod mechanism of action ( Gonzalez-Martinez et al, 2022 ). EML4-ALK is a chimeric receptor tyrosine kinase, hyperactivation of which drives cancer.…”
Section: Classification Of C-modsmentioning
confidence: 99%
“…Drug resistance to EML4-ALK-targeted therapies results in a post-therapy rescue of EGFR signaling. Activators of EGFR signaling are sequestered and inactivated by EML4-ALK condensates ( Gonzalez-Martinez et al, 2022 ). Upon treatment with EML4-ALK inhibitor and localizer c-mod cirzotinib ( Table 1 and shown in Figure 2A ), the EGFR activators are re-localized away from the EML4-ALK condensate community resulting in an active EGFR signaling driven drug resistance.…”
Section: Classification Of C-modsmentioning
confidence: 99%
See 1 more Smart Citation